Space Security and Legal Aspects of Active Debris Removal - Froehlich, Annette; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book analyzes the various legal and political concepts to resolve the problem of the existing space debris in outer space and which measures have been taken to avoid space debris or to reduce potential space debris in the course of future space missions. From a scientific and technical point of view various studies are ongoing to analyze the feasibility of active debris removal. Nevertheless it has to be highlighted that outer space is an international area where various actors with different legal and political concepts are operating, a situation that leads to different approaches concerning such activities.
Defining space debris (objects) in order to be able to remove them -- Dangers of space debris and reasons to deal with it urgently -- Environmental law as general obligation to reduce space debris -- Industrial commitments of legal aspects on active debris removal -- Acceptance of law should be admitted without punishment to resolve the space debris problem -- Jurisdiction and control aspects of space debris removal -- Space debris: untouchable lethal orbiting clouds -- Legal analysis of debris removal of small satellites in space -- ADR: a joint task and obligation to cooperate for the benefit of Mankind -- Right to self-defence in space -- Degree of the lack of regulation of space debris within the current space law regime -- Establishment of an international mechanism to deal with active debris removal -- Dispute resolution in the context of active debris removal -- Establishment of an international mechanism to deal with active debris removal -- Country overviews.
Keywords: Law of the sea; International law; Aeronautics -- Law and legislation; Political science; Solar system; Law of the Sea, Air and Outer Space; Political Science; Space Physics